1979
DOI: 10.1128/iai.25.3.1075-1077.1979
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific T-lymphocyte mitogenesis by pyrogenic exotoxins from group A streptococci and Staphylococcus aureus

Abstract: Group A streptococcal pyrogenic exotoxins types A, B, and C and staphylococcal pyrogenic exotoxin were shown to be potent nonspecific T-lymphocyte mitogens. Adherent cell populations did not significantly affect the nonspecific mitogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 14 publications
(9 reference statements)
1
22
0
Order By: Relevance
“…Furthermore, PE type C has profound effects on the host immune system, including nonspecific stimulation of T lymphocytes (19), suppression of immunoglobulin M synthesis (19), and enhancement of acquired hypersensitivity to induce a skin rash. These properties are shared by all PEs thus far described (2,4,5,8,12,17,18).…”
mentioning
confidence: 89%
“…Furthermore, PE type C has profound effects on the host immune system, including nonspecific stimulation of T lymphocytes (19), suppression of immunoglobulin M synthesis (19), and enhancement of acquired hypersensitivity to induce a skin rash. These properties are shared by all PEs thus far described (2,4,5,8,12,17,18).…”
mentioning
confidence: 89%
“…tococcus pyogenes have been shown to be T-cell mitogens, capable of activating T cells which can suppress the immune response (3,9,10,25,26,28). The enterotoxin from Vibrio cholerae can also enhance or suppress the immune response which is dependent on the timing of toxin administration relative to antigen stimulation (13,16).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Schlievert et al (34,35) reported that a pyrogenic exotoxin from S. aureus as well as from Streptococcus pyogenes has mitogenic activity for human T lymphocytes and rabbit splenocytes. No information on the production of pyrogenic toxin(s) by S. aureus L-forms, is available, but the data from this study as a whole suggest only a slight, if any, possibility that pyrogenic exotoxin is involved in our preparations .…”
Section: Discussionmentioning
confidence: 99%